Cancer cell-intrinsic expression of MHC II in lung cancer cell lines is actively restricted by MEK/ERK signaling and epigenetic mechanisms - Neuwelt, Alexander J (J Immunother Cancer, 2020)
BACKGROUND: Programmed death 1/programmed death ligand 1 (PD-1/PD-L1) targeted immunotherapy affords clinical benefit in ~20% of unselected patients with lung cancer. The factor(s) that determine whether a tumor responds or fails to respond to immunotherapy remains an active area of investigation. We have previously defined divergent responsiveness of two KRAS-mutant cell lines to PD-1/PD-L1 blockade using an orthotopic, immunocompetent mouse model. Responsiveness to PD-1/PD-L1 checkpoint blockade correlates with an interferon gamma (IFNγ)-inducible gene signature and major histocompatibility complex class II (MHC II) expression by cancer cells. In the current study, we aim to identify therapeutic targets that can be manipulated in order to enhance cancer-cell-specific MHC II expression. METHODS: Responsiveness to IFNγ and induction of MHC II expression was assessed after various treatment conditions in mouse and human non-small cell lung cancer (NSCLC) cell lines using mass cytometric and flow cytometric analysis. RESULTS: Single-cell analysis using mass and flow cytometry demonstrated that IFNγ consistently induced PD-L1 and MHC class I (MHC I) across multiple murine and human NSCLC cell lines. In contrast, MHC II showed highly variable induction following IFNγ treatment both between lines and within lines. In mouse models of NSCLC, MHC II induction was inversely correlated with basal levels of phosphorylated extracellular signal-regulated kinase (ERK) 1/2, suggesting potential mitogen-activated protein (MAP) kinase-dependent antagonism of MHC II expression. To test this, cell lines were subjected to varying levels of stimulation with IFNγ, and assessed for MHC II expression in the presence or absence of mitogen-activated protein kinase kinase (MEK) inhibitors. IFNγ treatment in the presence of MEK inhibitors significantly enhanced MHC II induction across multiple lung cancer lines, with minimal impact on expression of either PD-L1 or MHC I. Inhibition of histone deacetylases (HDACs) also enhanced MHC II expression to a more modest extent. Combined MEK and HDAC inhibition led to greater MHC II expression than either treatment alone. CONCLUSIONS: These studies emphasize the active inhibitory role that epigenetic and ERK signaling cascades have in restricting cancer cell-intrinsic MHC II expression in NSCLC, and suggest that combinatorial blockade of these pathways may engender new responsiveness to checkpoint therapies.